Infección con el virus de la inmunodeficiencia felina: desarrollo y aplicación de una técnica de doble reacción en cadena de la polimerasa (PRC) para el diagnóstico - Oliva, Graciela A. (2000)
A Nested PCR technique for direct identification of Feline Immunodeficiency Virus (FIV) was developed. Two methods for proviral DNA extraction and two pairs of primers were evaluated. The method for amplification was standardized and its specificity was determined by the restriction endonucleases digestion of PCR products. Antibodies specific to FIV were determined using a commercial kit. Thirty heparinized blood samples obtained from cats with and without clinical signs consistent with FIV infection were analyzed. In 17 of the samples antibodies specific to FIV and proviral DNA were detected. The PCR technique proved sensitive and specific. It could be useful in the presence of doubtful serologic results and to detect provirus in cats with recent infections.